2018
DOI: 10.1111/jcmm.13754
|View full text |Cite|
|
Sign up to set email alerts
|

Knockdown of lncRNA AK139328 alleviates myocardial ischaemia/reperfusion injury in diabetic mice via modulating miR‐204‐3p and inhibiting autophagy

Abstract: This study was aimed at investigating the effects of lncRNA AK139328 on myocardial ischaemia/reperfusion injury (MIRI) in diabetic mice. Ischaemia/reperfusion (I/R) model was constructed in normal mice (NM) and diabetic mice (DM). Microarray analysis was utilized to identify lncRNA AK139328 overexpressed in DM after myocardial ischaemia/reperfusion (MI/R). RT‐qPCR assay was utilized to investigate the expressions of lncRNA AK139328 and miR‐204‐3p in cardiomyocyte and tissues. Left ventricular end diastolic dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 27 publications
1
85
0
Order By: Relevance
“…Excessive inhibition of Beclin1 markedly increases cardiomyocyte death in response to hypoxia/reoxygenation injury (Issa et al, 2018). However, it has also been reported that different mechanisms to inhibit autophagy also protect against myocardial ischemia/reperfusion injury (Wu et al, 2018;Yu et al, 2018). It has been found that application of 3-MA to inhibit autophagy alleviates astrocyte injury by inhibiting LMP (Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive inhibition of Beclin1 markedly increases cardiomyocyte death in response to hypoxia/reoxygenation injury (Issa et al, 2018). However, it has also been reported that different mechanisms to inhibit autophagy also protect against myocardial ischemia/reperfusion injury (Wu et al, 2018;Yu et al, 2018). It has been found that application of 3-MA to inhibit autophagy alleviates astrocyte injury by inhibiting LMP (Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Yu et al [35] showed that silencing lncRNA AK139328 signi cantly increased miR-204-3p expression and inhibited autophagy of cardiomyocyte, thereby reducing myocardial ischemia/reperfusion injury (MIRI) in diabetic mice. Comparably, Xiao et al [36] discovered that ischemiareperfusion (IR) could down-regulate miR-204, while up-regulated the proportion of LC3-II protein and autophagy cell.…”
Section: Mirna-204 May Play a Critical Role In Cardiovascular Diseasesmentioning
confidence: 99%
“…For instance, L. H. Liu, Yue, et al (2016) Recently, researchers suggested that lncRNAs may regulate gene expression and tumor progression through regulating miRNA expression (Li, Hu, et al, 2016;. For instances, S. Yu et al (2018) indicated that knockdown of lncRNA AK139328 alleviated myocardial reperfusion/ischemia injury through regulating miR-204-3p and suppressing autophagy. Jiang et al (2018) showed that lncRNA TPT1-AS1 induced cell proliferation and metastasis through playing as a sponge of miR-324-5p in cervical cancer.…”
Section: The Expression Of Mir-214-3p Was Increased In the Bladdermentioning
confidence: 99%